2016
DOI: 10.7150/thno.13502
|View full text |Cite
|
Sign up to set email alerts
|

Measuring HER2-Receptor Expression In Metastatic Breast Cancer Using [68Ga]ABY-025 Affibody PET/CT

Abstract: Purpose: Positron Emission Tomography (PET) imaging of HER2 expression could potentially be used to select patients for HER2-targed therapy, predict response based on uptake and be used for monitoring. In this phase I/II study the HER2-binding Affibody molecule ABY-025 was labeled with 68Ga-gallium ([68Ga]ABY-025) for PET to study effect of peptide mass, test-retest variability and correlation of quantified uptake in tumors to histopathology.Experimental design: Sixteen women with known metastatic breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
258
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 222 publications
(276 citation statements)
references
References 29 publications
8
258
1
9
Order By: Relevance
“…52 Advantage of higher injected protein dose in discrimination between metastases with high and low HER2 expression has been confirmed also in a clinical study. 32 The saturable binding to two HER2-expressing cell lines in vitro demonstrated that binding specificity of the conjugates is preserved. A study using LS174T and SKOV-3 cell lines demonstrated similar cellular processing level and slow internalization of all conjugates (Figures 3 and 4).…”
Section: Comparative In Vivo Studiesmentioning
confidence: 98%
“…52 Advantage of higher injected protein dose in discrimination between metastases with high and low HER2 expression has been confirmed also in a clinical study. 32 The saturable binding to two HER2-expressing cell lines in vitro demonstrated that binding specificity of the conjugates is preserved. A study using LS174T and SKOV-3 cell lines demonstrated similar cellular processing level and slow internalization of all conjugates (Figures 3 and 4).…”
Section: Comparative In Vivo Studiesmentioning
confidence: 98%
“…The effective radiation doses were 0.15 6 0.02 mSv/MBq (21 mSv/patient) for 111 In and 0.028 6 0.003 mSv/MBq (5.6 mSv/patient) for 68 Ga (20,22). Injection of 500 mg of 68 Ga-ABY-025 provided better sensitivity and specificity than 100 mg, mainly because of reduced retention in the liver (21). Comparison with immunohistochemical staining of biopsy material demonstrated that the measurement of the maximal uptake value at 2-4 h after injection permits clear discrimination between metastases with 31 and 21 levels of HER2 expression (21).…”
Section: Affibody Molecules In Radionuclide Imagingmentioning
confidence: 99%
“…The second-generation Affibody molecule ABY-025 labeled with 111 In for SPECT imaging and 68 Ga for PET imaging were evaluated in phase I/II clinical studies for assessment of HER2 expression in breast cancer metastases (Fig. 1C) (20,21). ABY-025 was found to be safe in humans, and no anti-Affibody antibodies were found after repeated administration.…”
Section: Affibody Molecules In Radionuclide Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Ga-ABY-025 and PET have, in a recent study, been shown capable of discriminating HER2-positive metastases, with SUV correlating well with HER2 expression (17). In that study, 2 different amounts of peptides were administered, with the higher peptide dose giving the best results in terms of detectability and discrimination.…”
mentioning
confidence: 99%